Sosialisasi Stress Management Berbasis Aktivitas Fisik Untuk Penguatan Human Capital Masyarakat Di Era Digital - Mirzani Ahmad; Faizal Rizky Yuttama (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
The digital era is characterized by increasing demands of daily productivity, accelerated life pace, and multiple social roles that contribute to higher levels of psychological stress within society. Unmanaged stress may negatively affect mental well-being, physical health, and individual productivity as part of community human capital. This community service activity aimed to increase public awareness and understanding of stress, its impacts, and the role of physical activity, particularly muscle-strengthening exercises, as a non-pharmacological strategy for stress management. The activity was conducted through an educational socialization program for residents of Griya Satria Bukit Nirwana Housing Area via a community women’s forum. The method involved interactive material delivery, discussion, and question-and-answer sessions focusing on stress awareness and simple, safe physical activities that can be practiced independently at home. The results showed an improvement in participants’ understanding of stress management and the benefits of physical activity for mental well-being. Participants perceived muscle-strengthening exercises as accessible and applicable for daily stress management across different age groups. In conclusion, socialization-based stress management through physical activity is a relevant and practical approach to support community human capital strengthening in the digital era.